1985
DOI: 10.1007/bf00270764
|View full text |Cite
|
Sign up to set email alerts
|

Subdural empyema in infant meningitis: diagnosis, therapy, and prognosis

Abstract: Collections of subdural fluid during the course of infant Hemophilus influenzae meningitis have been demonstrated in the past by routine subdural taps and, more recently, by computed tomography. While the fluid is usually a benign effusion, the clinical picture and CT pattern may suggest a subdural abscess (empyema) necessitating further subdural punctures. This is a review of nine infants with subdural empyema. As reported in the literature, a remarkably good prognosis is apparent following treatment with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Bur hole drainage and craniotomy have been used for the drainage of SDE. 6,13 In literature reviews, intermittent transfontanel needle aspiration of the SDE may provide a means of removal of pus, 5,13 but it must be performed with great caution. Some pediatric series emphasized the importance of craniotomy in achieving a better outcome.…”
Section: Treatment Of Sdementioning
confidence: 99%
“…Bur hole drainage and craniotomy have been used for the drainage of SDE. 6,13 In literature reviews, intermittent transfontanel needle aspiration of the SDE may provide a means of removal of pus, 5,13 but it must be performed with great caution. Some pediatric series emphasized the importance of craniotomy in achieving a better outcome.…”
Section: Treatment Of Sdementioning
confidence: 99%
“…Curless[3] recorded negative culture stains in some of his patients who had H. Influenza meningitis. Eighteen of 37 cultures performed by Mauser and Tulleken[12] were sterile.…”
Section: Discussionmentioning
confidence: 99%
“…Curless[3] on the other hand reported that repeated subdural taps produced satisfactory results in eight of nine patients in his series. Diagnoses in these patients were done using CT scan in some and subdural taps in others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations